Data Integration in Poplar: ‘Omics Layers and Integration Strategies - Weighill, Deborah; Tschaplinski, Timothy J.; Tuskan, Gerald A.; Jacobson, Daniel (Frontiers in Genetics, 2019)
Populus trichocarpa is an important biofuels feedstock that has been the target of extensive research, and is emerging as a model organism for plants, especially woody perennials. This research has generated several large `omics datasets. However, only few studies in Populus have attempted to integrate various data types. This review will summarize various `omics data layers, focusing on their application in Populus species. Subsequently, network and signal processing techniques for the integration and analysis of these data types will be discussed, with particular reference to examples in Populus.